ANALISIS KEEFEKTIFAN SISTEM ELEKTRONIK DAN PELAYANAN PERPAJAKAN (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Raba Bima, NTB) - Widanarni Pudijiastuti; Djoko Sugiono (Universitas Riau Kepulauan, 2022)
Abstract In general, this study aims to determine the practice of electronic (online) taxation systems with indicators of the implementation of the e-filling system and tax services. Specifically, this study aims to determine the extent to which the effectiveness of the application of an electronic taxation system (online) and tax services affects tax revenue. The type of data used in this study is secondary data. This research is a type of qualitative descriptive research using three data collection techniques, namely observation, interviews, and documentation.The results of this study indicate that (1) the effectiveness of the application of an electronic (online) taxation system at KPP Pratama Raba Bima is seen from several aspects including the ease of using technology, time efficiency and administration, system readiness, security, and convenience, and the services provided by officers can say to have been effective. (2) The application of the electronic (online) tax system still affects optimizing revenue at the Raba Bima Pratama Tax Service Office but not too high. The application of an electronic (online) tax system has a role as a medium to facilitate tax service providers to more quickly determine strategies to maximize tax revenue.Keywords: effectiveness, electronic tax system, tax revenue